The Analysis of Knowledge Sharing and Learning Organization on Employee Performance at Hotel Midtown Surabaya - Siti Hotiah Bin Slamet Binti Dewi Setyowati; Gendut Sukarno (Jurnal Ekonomi dan Bisnis Digital, 2023)
Knowledge sharing plays an important role in improving the skills of everyone in the organization, because by sharing knowledge, it can be easily transferred, installed and developed efficiently. Learning Organization is an ongoing process within an organization that provides smooth learning and individual development for all employees or employees. The purpose of this study was to analyze and test the effect of knowledge sharing and learning organization variables on employee performance at Hotel Midtown Surabaya. The research method uses quantitative methods. The technique used is saturated sampling technique, with a total of 45 respondents taken from housekeeping division employees at the Hotel Midtown Surabaya. The data analysis technique uses the Partial Least Square-Structural Equation Model (PLS-SEM) with the SmartPLS analysis tool. The results of this analysis show that knowledge sharing contributes to employee performance, learning organization also contributes to employee performance.